Precerebellar cell groups in the hindbrain of the mouse defined by retrograde tracing and correlated with Wnt1-cre genetic labeling - Fu, Y.; Tvrdik, P.; Makki, N.; Paxinos, G.; Watson, Charles (Springer, 2011)
The precerebellar nuclei are hindbrain and spinal cord centers that send fibers to the cerebellum. The neurons of the major hindbrain precerebellar nuclei are derived from the rhombic lip. Wnt1, a developmentally important gene involved in intercellular signaling, is expressed in the developing rhombic lip. We sought to investigate the relationship between the cell clusters expressing Wnt1 and the precerebellar nuclei in the hindbrain. We therefore defined the hindbrain precerebellar nuclei by retrograde tracing, following cerebellar injections of HRP, and compared these results with the cell clusters expressing Wnt1 in newborn mice. We found that 39 distinct hindbrain nuclei project to the cerebellum. Of these nuclei, all but three (namely the oral pontine reticular nucleus, the caudal pontine reticular nucleus, and the subcoeruleus nucleus) contain neurons expressing Wnt1. This shows a high degree of overlap between the precerebellar nuclei and the nuclei that express Wnt1. However, it should be noted that neurons expressing Wnt1 are also found in the superior olivary complex, which is a basal plate derivative lacking cerebellar projections.